2020
DOI: 10.1177/1941738120938007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plyometric Training on Sport Performance in Adolescent Overhead Athletes: A Systematic Review

Abstract: Context: Plyometric training has been shown to be beneficial in adolescent overhead athletes. However, existing research on the effects of plyometrics on sport performance has been limited. Objective: To systematically review the current literature to investigate whether plyometric training intervention improves upper- and lower-body sport performance. Data Sources: Two electronic databases (MEDLINE and Web of Science) were searched using specific Medical Subject Headings (MeSH) terms up to February 2019, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
(145 reference statements)
3
11
0
1
Order By: Relevance
“…The current findings are consistent with other published studies examining efficacy of plyometric training in slightly older children than in the present study (Bedoya et al, 2015;Eraslan et al, 2021). To the best of our knowledge, only two studies (Chaouachi et al, 2014;Nobre et al, 2017) have applied a plyometric-based program on school premises, outside of the PE curriculum, in a slightly older sample than in the current study, and both identified significant improvements in motor performance skills.…”
Section: Discussionsupporting
confidence: 93%
“…The current findings are consistent with other published studies examining efficacy of plyometric training in slightly older children than in the present study (Bedoya et al, 2015;Eraslan et al, 2021). To the best of our knowledge, only two studies (Chaouachi et al, 2014;Nobre et al, 2017) have applied a plyometric-based program on school premises, outside of the PE curriculum, in a slightly older sample than in the current study, and both identified significant improvements in motor performance skills.…”
Section: Discussionsupporting
confidence: 93%
“…To perform these movements successfully, high levels of physical fitness, including speed, power, and agility are essential [ 1 ]. Furthermore, overhead sports such as baseball involve repetitive, high-intensity, whole-body movements, so adolescent athletes playing such sports should enhance their multi-dimensional exercise capacity, including the anaerobic power and agility of the upper and lower extremities [ 2 - 4 ]. A number of studies have thus highlighted that suitable training programs for adolescent overhead athletes are crucial to enhance sport-specific performance [ 4 ], and that various training programs have assisted in maintaining high-level performance and preventing injuries [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…those who did not do additional plyometric training [5]. Although the performance benefits of plyometric training are frequently shown in the literature [6,7], more studies are needed to understand the effects of different training methods on athletes of certain age groups and branches. In addition, when using this training method, it should be remembered that the inability to set exercise levels correctly can lead to injuries, so the selection of the exercises according to age and performance level is important.…”
Section: Original Articlementioning
confidence: 99%